WAKTU ANTARA BUS TRANS METRO BANDUNG KORIDOR CICAHEUM-CIBEUREUM - Ramdhan, Bella Pamuji; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Headway is an important factor for public transport users and operators, since headway is one of the quality of service indicators of public transportation system. The purpose of this study is to describe the headway of bus Trans Metro Bandung (TMB) in the corridor of Cicaheum-Cibeureum and analyze the headway distribution. The statistical distribution of TMB’s headway in each shelter has similardistribution, namely the gamma distribution with average as much as 27 minutes. Study results show that the headwaydistribution for one week data observation has gamma distribution with average as much as 27 minutes.